2018
DOI: 10.26434/chemrxiv.6852617.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optoregulated Protein Release from an Engineered Living Material

Abstract: An engineered living material for light-regulated protein release is realized by combining optogenetics, bacterial protein secretion and hydrogels. Hydrogel-immobilized bacteria are optogenetically programmed to express and secrete a fluorescent protein in response to light irradiation. Using light, tunability and localized confinement of protein expression along with dosing of protein release are demonstrated.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These strategies are based on the administration of material-embedded drug-producing bacteria or mammalian cells to provide sustained and patient-adapted delivery of therapeutic compounds. Recently, the Sankaran and Del Campo groups developed bacteria-based ELMs to produce therapeutic compounds in response to optical stimuli [ 274 , 275 ]. As host cells, endotoxin-free E. coli (ClearColi) were used, the outer membrane lipopolysaccharides of which have genetically been modified to avoid an endotoxin response in humans [ 276 ].…”
Section: Elmsmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies are based on the administration of material-embedded drug-producing bacteria or mammalian cells to provide sustained and patient-adapted delivery of therapeutic compounds. Recently, the Sankaran and Del Campo groups developed bacteria-based ELMs to produce therapeutic compounds in response to optical stimuli [ 274 , 275 ]. As host cells, endotoxin-free E. coli (ClearColi) were used, the outer membrane lipopolysaccharides of which have genetically been modified to avoid an endotoxin response in humans [ 276 ].…”
Section: Elmsmentioning
confidence: 99%
“…As host cells, endotoxin-free E. coli (ClearColi) were used, the outer membrane lipopolysaccharides of which have genetically been modified to avoid an endotoxin response in humans [ 276 ]. They transformed ClearColi with the blue light–responsive pDawn gene expression system to produce the red fluorescent protein as a model compound [ 274 ] or to express the vio-ABCE operon for the synthesis of the antimicrobial and antitumoral drug deoxyviolacein [ 275 ]. The engineered cells were embedded in either chemically crosslinked polyacrylamide or physically crosslinked agarose.…”
Section: Elmsmentioning
confidence: 99%
“…A previous report using a red fluorescent protein showed that protein expression with the pDawn system is detectable after 1 -2 hours of pulse cycled irradiation. 24,44 We estimate that due to the weak autofluorescence of dVio, higher expression levels are necessary for detection. Increasing pulse cycles led to an increasing fluorescence in the exposed area which reaches a saturation value after 9 hours exposure (Figure 3b).…”
mentioning
confidence: 99%